Implementasi Urgensi Pendidikan Islam dalam Interaksi Sosial di SMK Nurul Hikmah Sangatta Utara - Muhammad Yasin; Siti Aminah W. Tukan; Octaviani Lestari; Dian Nur Azikin (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to explore and analyze the implementation of the urgency of Islamic education in social interactions at Nurul Hikmah Sangatta Utara Vocational School. A qualitative approach was used to gain an in-depth understanding of how Islamic values ​​are applied in the school environment and their impact on students' social interactions. Data was collected through in-depth interviews, participant observation, and document analysis. The research results show that Islamic education at Nurul Hikmah Vocational School does not only focus on cognitive aspects, but also on developing students' character and morals. The implementation of Islamic education has proven effective in forming harmonious, respectful and tolerant social interactions among students. Values ​​such as honesty, responsibility and empathy are taught through various curricular and extracurricular activities. This research concludes that the urgency of Islamic education in shaping social interaction at Nurul Hikmah Vocational School is very significant and can be used as a model for other Islamic-based schools. The recommendation for educators and school administrators is to continue to strengthen the integration of Islamic values ​​in all aspects of education in order to create a social environment that is conducive to the development of student character.